2021
DOI: 10.48550/arxiv.2105.13369
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unitary channel discrimination beyond group structures: Advantages of sequential and indefinite-causal-order strategies

Jessica Bavaresco,
Mio Murao,
Marco Túlio Quintino

Abstract: For minimum-error channel discrimination tasks that involve only unitary channels, we show that sequential strategies may outperform parallel ones. Additionally, we show that general strategies that involve indefinite causal order are also advantageous for this task. However, for the task of discriminating a uniformly distributed set of unitary channels that forms a group, we show that parallel strategies are indeed optimal, even when compared to general strategies. We also show that strategies based on the qu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…More recently, however, there has been a growing interest in an extended class of theories, where processes can themselves evolve under a higher level type of operations called supermaps [15,16,22,20,26,67,12]. In quantum information, the development of supermaps stimulated the study of new protocols involving the manipulation of quantum processes and quantum causal structures [21,10,11,44,19,60,74,18,35,5,52,1,90,27,75,69,70,93,79,62,63,87,8,9,42,43,92,71,50,51]. In addition, quantum supermaps serve as a lens through which one can examine the kinds of causal structures which are compatible with quantum theory [54,25,66,20,14].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, however, there has been a growing interest in an extended class of theories, where processes can themselves evolve under a higher level type of operations called supermaps [15,16,22,20,26,67,12]. In quantum information, the development of supermaps stimulated the study of new protocols involving the manipulation of quantum processes and quantum causal structures [21,10,11,44,19,60,74,18,35,5,52,1,90,27,75,69,70,93,79,62,63,87,8,9,42,43,92,71,50,51]. In addition, quantum supermaps serve as a lens through which one can examine the kinds of causal structures which are compatible with quantum theory [54,25,66,20,14].…”
Section: Introductionmentioning
confidence: 99%
“…The study of such causal structures has shown that indefinite causal order brings advantages to the performance of several quantum information tasks [10][11][12][13][14][15][16][17][18][19]. From a fundamental perspective, the investigation of quantum causal structures not only renews our understanding of causality in nature but also helps to address the long-standing problem of reconciling quantum theory and general relativity in a theory of quantum gravity [20][21][22].…”
mentioning
confidence: 99%